Antimicrobial resistance and genetic diversity of Klebsiella pneumoniae strains from different clinical sources in horses - Gravey, Francois; Sévin, Corinne; Castagnet, Sophie; Foucher, Nathalie; Maillard, Karine; Tapprest, Jackie; Léon, Albertine; Langlois, Bénédicte; Le Hello, Simon; Petry, Sandrine (Frontiers in Microbiology, 2024)
Klebsiella pneumoniae is a major cause of infections and reproductive disorders among horses, ranked in recent French studies as the sixth most frequently isolated bacterial pathogen in equine clinical samples. The proportion of multidrug-resistant (MDR) K. pneumoniae is therefore significant in a context where MDR K. pneumoniae strains are considered a major global concern by the World Health Organization. In this study, we used a genomic approach to characterize a population of 119 equine K. pneumoniae strains collected by two laboratories specialized in animal health in Normandy (France). We describe the main antibiotic resistance profiles and acquired resistance genes, and specify the proportion of virulence-encoding genes carried by these strains. The originality of our panel of strains lies in the broad collection period covered, ranging from 1996 to 2020, and the variety of sample sources: necropsies, suspected bacterial infections (e.g., genital, wound, allantochorion, and umbilical artery samples), and contagious equine metritis analyses. Our results reveal a remarkable level of genomic diversity among the strains studied and we report the presence of 39% MDR and 9% hypervirulent strains (including 5% that are both MDR and hypervirulent). These findings clearly emphasize the importance of improving the surveillance of K. pneumoniae in routine equine diagnostic tests to detect high-risk MDR-hypervirulent Klebsiella pneumoniae strains. The circulation of these worrisome strains reveals that they are not being detected by the simple K1, K2, and K5 serotype approach currently implemented in the French horse-breeding sector.